Fraud Hexagon dalam Mendeteksi Financial Statement Fraud Perusahaan Perbankan di Indonesia - Handoko, Bambang Leo (Universitas Swadaya Gunung Jati, 2021)
AbstractCases of fraud are increasing from year to year and the costliest type of fraud is financial statement fraud which causes substantial losses for the company and users of financial statement. The aim of this research is to analyze fraud hexagon on detecting financial statement fraud of banking companies listed in Indonesia Stock Exchange for the period 2015-2019. The research population is 46 banking companies listed in Indonesia Stock Exchange. Purposive sampling method is used on this research. The sample chosen with matching criteria is 41 companies with a total observation of 205. Logistic regression method is used to analyze data and data processing was performed with IBM SPSS 26. The research results indicated that the financial target, external pressure, ineffective monitoring, change in auditor, change in director, and frequent number of CEO’s picture do not have an effect in detecting financial statement fraud on listed banking companies. Meanwhile, collusion has an effect in detecting financial statement fraud on listed banking companies.Keywords: Fraud hexagon; Financial statement fraud; Banking company. Abstrak Kasus kecurangan mengalami peningkatan dari tahun ke tahun dan yang paling merugikan ialah kecurangan laporan keuangan serta menyebabkan kerugian bagi perusahaan dan bagi pengguna laporan keuangan. Penelitian ini bertujuan untuk menganalisis faktor-faktor fraud hexagon dalam mendeteksi financial statement fraud pada perusahaan sektor perbankan yang terdaftar di Bursa Efek Indonesia (BEI) periode 2015-2019. Populasi yang digunakan adalah 46 perusahaan sektor perbankan yang terdaftar di Bursa Efek Indonesia. Metode purposive sampling merupakan metode pengambilan sampel yang digunakan dalam penelitian ini. Sampel yang memenuhi kriteria penelitian adalah 41 perusahaan perbankan dengan total observasi adalah sebanyak 205. Metode analisis data menggunakan metode regresi logistik dengan bantuan aplikasi IBM SPSS 26 untuk melakukan pengujian data. Hasil penelitian menunjukkan bahwa financial target, external pressure, ineffective monitoring, change in auditor, change in director, dan frequent number of CEO’s picture tidak memiliki pengaruh dalam mendeteksi financial statement fraud. Sedangkan, variabel collusion memiliki pengaruh dalam mendeteksi financial statement fraud.Kata Kunci: Fraud hexagon; Kecurangan laporan keuangan; Perusahaan perbankan.